Sistem Rekomendasi Menggunakan Algoritma Apriori Pada Aplikasi E-Commerce Toko Sudirman Sport - Ahmad Sukanda; Andri Andri (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
The System of selling and marketing products at the Sudirman Sport store which is still done conventionally causes the problem of lack of sales transactions obtained by the store because it only relies on buyers who come directly to the store. Meanwhile, many stores in Indonesia have implemented any system e-commerce in stores. The solution to this problem is to build a website-e-commerce application based for sales and marketing of products sold by the Sudirman Sport store and implement a marketing strategy, namely the System Recommendation Product attract buyers to buy products that have been offered by the Sudirman Sport store and combined with the a priori algorithm to get accuracy in the data processing process to help stores predict buyer interest in an item and then recommend it in order to attract buyers and increase product sales at the Sudirman sport store.